New magnetic graphene-based inorganic–organic sol-gel hybrid nanocomposite for simultaneous analysis of polar and non-polar organophosphorus pesticides from water samples using solid-phase extraction. (January 2017) - Rashidi Nodeh, Hamid; Wan Ibrahim, Wan Aini; Kamboh, Muhammad Afzal; Sanagi, Mohd Marsin
Abstract: A new graphene-based tetraethoxysilane-methyltrimethoxysilane sol-gel hybrid magnetic nanocomposite (Fe3 O4 @G-TEOS-MTMOS) was synthesised, characterized and successfully applied in magnetic solid-phase extraction (MSPE) for simultaneous analysis of polar and non-polar organophosphorus pesticides from several water samples. The Fe3 O4 @G-TEOS-MTMOS nanocomposite was characterized using Fourier transform-infrared spectroscopy, energy-dispersive X-ray spectroscopy, field emission scanning electron microscopy and X-ray diffraction. Separation, determination and quantification were achieved using gas chromatography coupled with micro electron capture detector. Adsorption capacity of the sorbent was calculated using Langmuir equation. MSPE was linear in the range 100–1000 pg mL −1 for phosphamidon and dimethoate, and 10–100 pg mL −1 for chlorpyrifos and diazinon, with limit of detection (S/N = 3) of 19.8, 23.7, 1.4 and 2.9 pg mL −1 for phosphamidon, dimethoate, diazinon and chlorpyrifos, respectively. The LODs obtained is well below the maximum residual level (100 pg mL −1 ) as set by European Union for pesticides in drinking water. Acceptable precision (%RSD) was achieved for intra-day (1.3–8.7%, n  = 3) and inter-day (7.6–17.8%, n  = 15) analyses. Fe3 O4 @G-TEOS-MTMOS showed high adsorption capacity (54.4–76.3 mg g −1 ) for the selected OPPs. No pesticide residues were detected in the water samples analysed. Excellent extraction recoveries (83–105%) were obtained for the spiked OPPs from tap, river, lake and sea water samples. The newly synthesised Fe3 O4 @G-TEOS-MTMOS showed high potential as adsorbent for OPPs analysis. Graphical abstract: Highlights: New sol-gel hybrid magnetic adsorbent synthesised for organophosphorus pesticides (OPPs). Fe3 O4 modified with graphene (G) and inorganic–organic sol-gel hybrid (TEOS-MTMOS). Fe3 O4 @G-TEOS-MTMOS used as new adsorbent for simultaneous preconcentration of OPPs. High extraction recovery (>80%) and high enrichment (>109) with Fe3 O4 @G-TEOS-MTMOS. 71 × lower LOD (than EU) with the new Fe3 O4 @G-TEOS-MTMOS for OPPs in water samples.